Does Innovation Affect Firm Value Study On Compas100 Index Companies For The 2016 - 2020 Period - Nanda Dwi Fitri; Suherman Suherman; Sholatia Dalimunthe (LPPPIPublishing, 2023)
The purpose of this study is to determine whether innovation has an impact on company value in the Kompas100 case study for the years 2016 to 2020. This study used purposive sampling to select 31 businesses for its sample. Secondary data were used, including annual reports and financial statements for each Kompas100 company from 2016 to 2020. Innovation using rnd costs is the independent variable in this study. The Tobin's Q proxy's value, on the other hand, serves as the study's dependent variable. This study found that innovation has no effect on company value.